STRATEGI SEKOLAH DALAM MEMANFAATKAN MEDIA TEKNOLOGI DIGITAL DALAM KEGIATAN PEMBELAJARAN DI MTS AL-HUSNA KOTA TANGERANG - Hamsah Tis'ah, J. Anhar Rabi; Fauzi, Achmad (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2024)
ABSTRACTThis study aims to determine the school's strategy for utilizing digital technology in learning activities at Madrasah Tsanawiyah Al-Husna Tangerang City. This type of research uses qualitative methods. This research was conducted at MTS Al-Husna Tangerang City with the aim of studying the use of digital technology media in learning and the factors that influence the use of digital technology in learning. The data collection techniques in this study are observation, interviews and documentation. The results of this study are the school's strategy for utilizing digital technology in learning, namely: introducing students to applications such as word and excel gradually and adjusting technology according to the times and market trends so that they are not left behind. Supporting factors in the use of digital technology at MTS Al-Husna. Namely: infocus, wifi, computer lab and students' cellphones. And as for the inhibiting factors in the use of digital technology in learning activities, namely: educators who do not understand technology (technological stuttering), lack of digital technology facilities, intermittent wifi, lack of time, and damage to digital technology tools Keywords: digital technology, school strategy, media